Development of learning instruments for the PJBL model in biotechnology through the Nila Pekasam project - Friza Isnaeni; Entin Daningsih; T. Titin (University of Muhammadiyah Malang, 2025)
Fish pekasam is a traditional fish fermentation product that can be used in biotechnology learning through the Project-Based Learning (PjBL) model. However, the use of PjBL by teachers remains low due to difficulties in developing learning instruments. This study aimet to develop PjBL learning instruments for making fish pekasam, reflecting local wisdom in West Kalimantan. This project is important because it provides contextual learning, connects with students' environment, integrates local wisdom, and helps preserving culture while enhancing students' practical biotechnology skills. The Research and Development (R&D) method was used, following five of Borg and Gall's ten steps that were modified: 1) identifying potential and problems, 2) data collection, 3) product design, 4) product validation, and 5) revision. Developed instruments included lesson plans, learning videos, student worksheets, assessment sheets, and evaluation questions, tailored to PjBL stages. Validation was done by five validators (2 UNTAN lecturers, 3 biology teachers) using Likert scale and CVR/CVI analysis. Results showed that all instruments achieved a CVI value of 1.00. However, some validators gave scores of 3 on certain criteria, indicating a need for revisions. Despite this, the instruments were deemed valid and ready for use in class XII Senior High School biotechnology lessons.